Implementing Shannon Entropy, SWOT and Mathematical Programming for Supplier Selection and Order Allocation - Mazaher Ghorbani; S. Mohammad Arabzad; Mahdi Bahrami (International Journal of Supply Chain Management, 2012)
Supplier selection is a multiple criteria decision making (MCDM) problem which is affected by several conflicting factors. In the business market of flaming competition in recent years, more attention has been paid to this problem. In this paper, a two-phased model is proposed for supplier selection and order allocation. At the first, suppliers are evaluated according to both qualitative and quantitative criteria resulting from SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis. SWOT is a useful technique in strategic management and is utilized to determine criteria and to deal with suppliers situation in competitive market. Defining the criteria, Shannon entropy is then used to calculate weight of criteria. Then the results are used as an input for integer linear programming (ILP) to allocate order to suppliers.